Faktor-Faktor Yang Mempengaruhi Kebijakan Utang dengan Profitabilitas sebagai Pemoderasi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Andy Andy; Giovanni Angeline; Yose Roberto; Henryanto Wijaya; Levina Febrianty (Jurnal Bina Akuntansi, 2023)
Dividend policies, asset structure, company size, growth, and profitability can all impact how manufacturing companies manage their debt. The research was conducted between 2017 and 2019 with a purposive sampling method of 37 manufacturers listed on the Indonesia Stock Exchange. The debt policy is the independent variable in this study, whereas the dependent variables are as follows: dividend policy, company performance, asset structure, and liquidity. Profitability serves as a moderating variable. The findings indicate that the dividend policy alongside liquidity has a significant impact on a company's debt policy, whereas asset structure, company size and growth, and profitability have no significant impact on debt policy. The profitability variable has little effect on the relationship between debt policy and dividend policy, asset structure, size, firm growth, and liquidity. This study summarizes the importance of prudent debt management in order to avoid an imbalance of internal and external resources.